KAJI EKSPERIMENTAL PENGARUH WAKTU PENAHANAN CAIR TERHADAP PEMBENTUKAN GRAFIT BULAT PADA PROSES PENGECORAN BESI COR NODULAR 700 - R Suratman; R Widodo (Mesin, 2000)
Nodular graphite on iron casting can be formed because of the present of Mg element from 0.02% - 0.05%, which is alloyed with iron base material to form FeSiMg through inoculation effect. At the pouring stage, especially in continuous production, Mg in the melting ï¬‚uid and its inoculation effect decrease so that the formed graphite will not round as expected and certainly weaken its mechanical properties.This writing discuss the maximum holding time for the melting ï¬‚uid in a ladle to assure acceptable mechanical properties, through experimental analysis of roundness of nodular graphite and tensile strength of the material by casting it in every 2 minutes right after adding the Mg element.By referring to the decreasing Mg, iron ï¬‚uid can be held up to 100 minutes, provided that the iron fluid contain maximum 0.01% Sulfur and maintained to the lowest holding temperature without ignoring pouring temperature standard for iron, maximum temperature in the ladle set 1400 "C. However, the tensile strength will be decreased to the acceptable value only up to 24 minutes, as a result of refraction of graphite that is affected by decreasing inoculation effect.